Rubber compositions for dynamic or static applications, methods for their preparation, and products incorporating same - Patents.com
The crosslinkable rubber composition with a thermoplastic polymer phase dispersed as filaments or fibrils addresses high hysteresis and nonlinearity issues, achieving superior mechanical properties and fatigue strength by processing above the polymer's crystallization or glass transition temperature.
Patent Information
- Application Number
- JP2024535854
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-17
- Filing Date
- 2022-12-13
- Publication Date
- 2025-01-22
AI Technical Summary
Existing rubber compositions reinforced with carbon black or silica suffer from high hysteresis losses and mechanical nonlinearity under dynamic stresses, leading to unsatisfactory stiffness changes and reduced fatigue strength, particularly at low temperatures.
A crosslinkable rubber composition is developed with a thermoplastic polymer phase dispersed as filaments or fibrils, processed above the crystallization or glass transition temperature of the polymer, followed by crosslinking, to enhance reinforcement and mechanical properties.
The composition exhibits improved Shore hardness, secant modulus, and fatigue strength, with reduced mechanical nonlinearity and enhanced dynamic properties, maintaining performance under thermal oxidative aging and UV exposure.
Smart Images

Figure 2025501506000007 
Figure 2025501506000008 
Figure 2025501506000009
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to a crosslinkable rubber composition, to a method for its preparation, to a crosslinked rubber composition, to a mechanical part with dynamic function and to a sealing element, at least part of which comprises this crosslinked rubber composition. The present invention applies in particular, but without limitation, to all industrial applications using crosslinked rubber compositions, including said mechanical part with dynamic function, in particular selected from anti-vibration supports and elastic joints for automobiles or industrial equipment, and said sealing element, in particular selected from sealings for automobile bodies and sealing profiles for buildings.
[0002] [Prior Art] Traditionally, the reinforcement of elastomers in rubber compositions is carried out by adding fillers (e.g. carbon black or silica) to improve the mechanical properties of the composition by hydrodynamic effects and by interactions between the elastomer and the filler on the one hand and between the fillers themselves on the other hand. These fillers, in powder form, are dispersed in the rubber by thermomechanical processing, during the mixing of the raw materials of the composition, except for the crosslinking system, by heating the mixture to a maximum temperature, usually below 150°C, usually between 100 and 130°C for carbon black-filled ethylene-propylene-diene terpolymer (EPDM) type rubbers.
[0003] However, these filler-elastomer and filler-filler interactions give rise to adverse effects associated with hysteretic losses, commonly referred to as the Payne effect, which is reflected by a nonlinearity, i.e., amplitude stiffening, and especially at low temperatures, of crosslinked rubber compositions subjected to dynamic stress. This stiffening is accompanied by dynamic properties that may prove unsatisfactory for said compositions, due to the above-mentioned interactions with the reinforcing fillers used, and these dynamic properties are determined by the complex shear modulus G of the composition at two dynamic strain amplitudes. * It is usually possible to evaluate the elastic modulus by measuring the ratio of the storage modulus G' to the complex modulus G * is G * =G´+iG´´; G´: Storage modulus or elastic modulus, G * where G' characterizes the stiffness or viscoelastic behavior of the composition (i.e., the energy stored and fully restored); and G´´: Loss modulus or dissipation modulus, G * It is provided that G" is the imaginary part of G", characterizes the viscous behavior of the composition (i.e. the energy dissipated in the form of heat) and the ratio G" / G" defines the loss tangent tan δ.
[0004] This ratio usually corresponds to G' measured at a low dynamic strain amplitude to G' measured at a high dynamic strain amplitude, the two moduli G' being measured at the same frequency and at the same temperature (for example G'0.5% / G'20%). It is known that G'0.5% / G'20% is usually between 1.80 and 2.00 (phr: parts by weight per 100 parts of elastomer) for a rubber composition based on polyisoprene (IR) and reinforced with 40 phr of N330 grade carbon black to be usable in dynamic applications. In fact, it is known that in reinforced materials, the viscoelastic behavior changes from small dynamic strain amplitudes, with a large decrease in G' with a large increase in strain.
[0005] In order to overcome the above-mentioned drawback of high hysteresis loss in conventionally filled compositions, US Patent 8247494B2 discloses a rubber composition that may not contain carbon black and silica and is reinforced with a thermoplastic resin dispersed in the form of discrete domains in a continuous phase of crosslinked olefinic rubber. The document teaches a method of crosslinking rubber exclusively by hydrosilylation to form silicone crosslinks.
[0006] US Patent 3965055A relates to a rubber composition in which a semi-crystalline thermoplastic resin (in the example polypropylene) is dispersed in an elastomer as particles with a cross-sectional dimension D of at most 500 nm and an aspect ratio (length L / D) at least equal to 2, by mixing above the melting point of the resin and then stress-free crosslinking of the composition below said melting point. More precisely, the mixture obtained by mixing step A is cooled below said melting point (for example to room temperature) during step B, the cooled mixture is then placed on another mixer, during step C, kept at a temperature sufficiently low to avoid scorching of the mixture, a crosslinking system is added to the mixture at a temperature of 150-170°F (65-93°C) in the example, and then in step D the composition obtained is molded below said melting point and the molded part is then crosslinked in step E. Thus, mechanical processing of the crosslinkable composition is carried out at low temperature during step C.
[0007] WO 2020 / 225498 A1 in the name of the applicant discloses a crosslinkable rubber composition based on an elastomer, comprising a crosslinking system and a thermoplastic phase having at least one melting point Tf and dispersed as nodules (for example spherical or ellipsoidal), the crosslinking system comprising sulfur if the elastomer is unsaturated and said phase comprises saturated chains, or a peroxide if the elastomer is saturated. The composition comprises: a) melt reaction of the elastomer with other ingredients, except for the crosslinking system, to produce a precursor mixture for the composition, involving heating the mixture by thermomechanical processing to a temperature above Tf, maintained for a holding time; b) mechanical processing of the precursor mixture with the addition of the crosslinking system to produce a crosslinkable composition; This includes products produced by.
[0008] The examples in WO2020 / 225498A1 show that the mechanical processing step b) (known as acceleration on rolls) is carried out on day D of the thermomechanical processing step a), after prior cooling of the precursor mixture obtained in a) from 160° C. to a temperature of 30° C. The process according to WO2020 / 225498A1 makes it possible to obtain, by means of the nodules, an improved resistance to scorching for crosslinkable compositions, and, for crosslinked compositions, the same degree of reinforcement and improved mechanical properties even after ageing by thermooxidation or via UV radiation, compared to a control composition based on the same raw materials, except for the carbon black contained instead of the thermoplastic phase.
[0009] In the course of its recent research, the Applicant sought to modify the mixing process according to these examples of WO 2020 / 225498 A1 in order to further improve in particular the mechanical properties of the resulting crosslinked rubber compositions.
[0010] DISCLOSURE OF THEINVENTION One object of the present invention is to propose a rubber composition which not only remedies the above-mentioned drawback of high hysteresis of carbon black- or silica-filled compositions, but also has in particular further improved reinforcing properties with respect to those of the compositions tested in WO 2020 / 225498 A1.
[0011] This object is achieved in that the Applicant has surprisingly found that if the above-mentioned step b) of the precursor mixture according to WO2020 / 225498A1 is modified such that the temperature Tb of the precursor mixture during mechanical processing is temporarily higher than the crystallization temperature Tc of the thermoplastic polymer phase, or the glass transition temperature Tg of the thermoplastic polymer phase, respectively, when said phase is partially crystalline or amorphous, a mixture is obtained which, after the addition of the crosslinking system, gives a crosslinkable composition in which said phase is homogeneously dispersed in the elastomeric matrix in the form of filaments or fibrils of specific morphological characteristics. It is this mechanical processing, optionally carried out temporarily above Tc or above Tg, that makes it possible to obtain, for the crosslinked composition, an increased hardness and improved reinforcement, reflected by overall superior static and dynamic mechanical properties (including fatigue strength), compared to the static and dynamic mechanical properties of a control composition of the same formulation (i.e. based on the same raw materials and amounts) but obtained via the process exemplified in WO2020 / 225498A1.
[0012] More precisely, the crosslinkable composition according to the invention is based on at least one elastomer, a crosslinked system and other ingredients including a thermoplastic polymer phase having at least one melting point Tf or softening point Tr, a glass transition temperature Tg and, if said phase is partially crystalline, a crystallization temperature Tc, the phase being dispersed in the at least one elastomer in the form of particles; said crosslinking system comprises sulfur if said at least one elastomer is unsaturated and said phase comprises saturated polymer chains, and comprises a peroxide if said at least one elastomer is saturated; The crosslinkable composition comprises a) a melt reaction to obtain a precursor mixture of the crosslinkable composition by thermomechanical processing of a reaction mixture comprising the at least one elastomer and the other ingredients, except for the crosslinking system, comprising heating the reaction mixture to a maximum temperature Ta of the reaction mixture, the maximum temperature Ta being higher than the at least one temperature Tf or Tr; then b) mechanical processing of the precursor mixture with the addition of the crosslinking system to produce the crosslinkable composition; This includes products produced by.
[0013] According to the invention, the particles comprise filaments or fibrils produced by these steps a) and b), The temperature Tb of the precursor mixture during the mechanical processing of step b) is temporarily higher than the crystallization temperature Tc if the thermoplastic polymer phase is partially crystalline or higher than the glass transition temperature Tg if the thermoplastic polymer phase is amorphous.
[0014] The term "based on" is used herein to mean that the composition or ingredient under consideration comprises a majority by weight of that component, i.e., a mass fraction of more than 50%, preferably more than 75%, which mass fraction may be up to 100%.
[0015] The terms "unsaturated" and "saturated" are understood in the embodiments described herein to mean, respectively, a thermoplastic elastomer / polymer that contains at least one unsaturation (i.e., a double or triple bond) and a thermoplastic elastomer / polymer that contains no unsaturation (i.e., no double or triple bonds).
[0016] As used herein, the term "partially crystalline thermoplastic polymer phase" means that this phase comprises at least one semi-crystalline thermoplastic polymer and thus has, in addition to a glass transition temperature Tg, at least a melting point Tf, a softening point Tr, and a crystallization temperature Tc (by definition, Tg <Tc<Tr<Tfである)。
[0017] In this specification, the term "amorphous thermoplastic polymer phase" means that this phase consists of at least one amorphous thermoplastic polymer that has a softening point Tr in addition to a glass transition temperature Tg (Tg <Tr)。
[0018] The term "filament or fibril" is used herein to mean an elongated fiber or fibrillated structure (e.g., nanofilament) that is distinct from a convex solid body such as a sphere or ellipsoid, and may, for example, have a generally constant lateral width along the length of the filament or fibril (which may be straight, angled, or curved).
[0019] Preferably, the particles dispersed in the composition according to the invention comprise said filaments or fibrils in a volume fraction of more than 70%, advantageously more than 80% or even more than 90%.
[0020] It should be noted that the crosslinkable composition according to the invention thus makes it unexpectedly possible to obtain a dispersion of this phase in the form of particles in an elastomeric matrix, by subsequent thermomechanical processing (with heating maintained for a given time), said mechanical processing being carried out at a temperature Tb of the mixture temporarily (i.e. for a given period) higher than a threshold Tc or Tg (threshold determined by the thermoplastic phase selected), said particles mainly comprising or consisting of these filaments or fibrils, with a further optimized interface between the particles and this matrix, thus endowing the composition with these improved reinforcing properties under static and dynamic stress.
[0021] Thus, as explained below, the crosslinkable composition according to the invention, following its thermal crosslinking via a crosslinking system added in step b) suitable for the thermoplastic elastomer-phase couple, makes it possible to impart to the crosslinked composition significantly improved Shore hardness and mechanical properties compared to those of the similarly formulated control composition obtained according to the examples of WO 2020 / 225498 A1.
[0022] In general, semi-crystalline or amorphous thermoplastic polymers can be used as the thermoplastic phase if they have a sufficiently high stiffness at room temperature and are plastic or at least deformable during mixing. As explained below, the stiffness can be reduced by increasing the temperature of the precursor mixture during the mechanical processing step b) above Tc in the case of an at least partially crystalline phase, or above Tg in the case of an amorphous phase (for example consisting of at least one polystyrene as the amorphous polymer, in this example Tg is typically between 80 and 105 °C).
[0023] It should also be noted that the compositions according to the present invention, characterized by a dispersion of a thermoplastic phase in said at least one elastomer, are not to be confused with thermoplastic vulcanizates in which the thermoplastic substrate contains a dispersion of rubber nodules.
[0024] Also, generally speaking, the duration of the heating in step a) may be at least 10 seconds, preferably between 10 seconds and 10 minutes, more preferentially between 20 seconds and 5 minutes, for example between 30 seconds and 3 minutes.
[0025] According to another feature of the invention, the mechanical processing of step b) may be started at an initial temperature Tb0 of the precursor mixture, When the thermoplastic polymer phase is partially crystalline or amorphous, T>T or T>T, respectively; Preferably, said mechanical working of step b) is initiated while said phase is in a molten or softened state in said precursor mixture.
[0026] It should be noted that the mechanical processing according to the invention may thus begin at a temperature Tb0 high enough for the thermoplastic phase to change from an amorphous or non-glassy state to a crystalline or glassy state, respectively, during step b), preferably this phase melting or at least softening in the precursor mixture, which phase may then soften or even be substantially liquid during the start of step b).
[0027] According to a preferred embodiment of the present invention, the temperature Tb of the precursor mixture during step b) is highest when machining is started, where Tb = Tb0, and then, when the thermoplastic phase is partially crystalline or amorphous, respectively, it drops to Tb < Tc or Tb < Tg.
[0028] It should be noted that during this decrease in Tb with time from the initial moment t0 corresponding to Tb = Tb0, the thermoplastic phase transitions from an amorphous or non-glassy state to a crystalline or glassy state, respectively, during the first few minutes of machining (i.e., at the start of step b).
[0029] Preferably, according to the preferred aspect of the present invention, machining is started at the initial temperature Tb0, The initial temperature Tb0 may coincide with Tc or Tg, respectively, and the dropping temperature Tt of the precursor mixture (e.g., "sharp dropping"), and the highest temperature Ta of the reaction mixture, depending on whether the thermoplastic polymer phase is partially crystalline or amorphous.
[0030] In other words, Tb0 is preferably between Tc and Ta, or between Tg and Ta, and preferably, Tb0 is 110 to 220 °C.
[0031] Even more preferably, Tb0 is 150 to 190 °C when the thermoplastic phase is partially crystalline (e.g., including a propylene homopolymer or copolymer) or amorphous (e.g., including polystyrene), The temperature Tb of the precursor mixture is highest at the start of mechanical processing, where Tb=Tb0, and then drops until Tb is, for example, 10-90° C. In this case, the final value of Tb is then lower than Tc or Tg as explained above, and this final value can vary significantly depending on the structure selected for the mixing and thermal regulation system.
[0032] In general, the crosslinking system is preferably added to the precursor mixture after a period of homogenization of the precursor mixture, The time (counted from the start of the mechanical processing) is, for example, 1 minute to 5 minutes, for example, 2 minutes to 4 minutes.
[0033] It is noted that the initial temperature Tb0 of the precursor mixture at which step b) is started may be such that the mechanical working begins when the precursor mixture is in a molten state (e.g. liquid or pasty) or at least softened, before the temperature Tb of the precursor mixture drops as explained above.
[0034] According to another general feature of the invention, step b) may follow step a) in such a way that the extraction of said precursor mixture at the end of step a) and the start of the mechanical processing in step b) after the transfer of said precursor mixture are separated by a time interval Δt, Bringing up a temperature difference ΔT=Tt-Tb0 between the dropping temperature Tt (e.g. "fast dropping") of the precursor mixture at the end of step a) and the initial temperature Tb0 at the beginning of step b), such that ΔT / Tt<30%, and preferably ΔT / Tt<20%.
[0035] Preferably, Δt<10 min (and more preferentially Δt<2 min), so that ΔT / Tt is less than 10%, and for example ΔT / Tt<1%, In a manner in which the precursor mixture is subjected to generally continuous shear from the start of step a) to the end of step b), the precursor mixture is then cooled at the end of step a) essentially during the mechanical processing in step b).
[0036] It should be noted that the invention can be demonstrated by the fact that the cooling of the precursor mixture from the point of extraction at the end of step a) is carried out essentially by this shear, i.e. without cooling substantially to room temperature pending mechanical processing.
[0037] According to a general aspect of the invention, the particles dispersed in the composition, which particles consist of said filaments or fibrils in a volume fraction of at least 70%, preferably at least 80% and more preferentially at least 90%, (a) Their equivalent diameter, defined as the diameter of a hypothetical spherical particle of the same volume, (i) for all said particles, an equivalent diameter ranging from 5 nm to 1000 nm, and preferably from 10 nm to 330 nm; (ii) a median equivalent diameter of 20 nm to 200 nm, preferably 30 nm to 60 nm; and (iii) an average equivalent diameter of 30 nm to 300 nm, and preferably 40 nm to 70 nm; and / or (b) their aspect ratio, defined as the ratio of the longest length of each of the particles to their shortest width; (i) an average aspect ratio of 2 or more, and preferably 2.0 to 2.5; and (ii) a maximum aspect ratio for all said particles greater than 5, preferably between 10 and 15; The morphological characteristics of the cellular component may be at least one of the following:
[0038] These particles may thus have features [(a)(i) and / or (a)(ii) and / or (a)(iii)] or / and [(b)(i) and / or (b)(ii)], advantageously at least (a)(iii) and (b)(i), which are measured by focused ion beam (FIB) scanning electron microscopy (SEM), a technique known as FIB-SEM (focused ion beam scanning electron microscopy).
[0039] Thus, the term "equivalent diameter" is used herein to mean the diameter of an equivalent sphere, which corresponds to the diameter of a sphere having the same volume as the particle itself, but not the same projected area. This equivalent diameter thus corresponds to the diameter of a hypothetical spherical particle of radius R and the same volume, i.e., this equivalent diameter is V=4 / 3·π·R 3 It is calculated from the volume V of a segmented object defined by
[0040] The term "mean equivalent diameter" is used herein to mean the arithmetic number mean of equivalent particle diameters, i.e., for a sample divided into classes. The term "median equivalent diameter" is used herein to mean the median of the volume distribution d 50 , i.e., by definition, the equivalent diameter corresponding to a cumulative frequency of 50% that divides a histogram of relative frequencies into two parts of equal area.
[0041] The term "average aspect ratio" as used herein means the arithmetic number average of the aspect ratios of the particles.
[0042] In general, the crosslinkable composition of the invention may comprise said thermoplastic phase in an amount ranging from 1 to 150 phr (phr: parts by weight per 100 parts of elastomer(s)), and preferably from 5 to 70 phr (even more preferentially from 10 to 30 phr).
[0043] According to another feature of the invention, the crosslinkable composition comprises, as a powder filler dispersed in said at least one elastomer, From 0 to 100 phr (preferably from 0 to 50 phr, even more preferentially from 0 to 10 phr, or even more preferably from 0 to 5 phr) of organic filler (e.g. carbon black); and 0 to 150 phr (e.g., 10 to 100 phr) of non-reinforcing inorganic fillers other than silica (phr: parts by weight per 100 parts of elastomer(s); may include:
[0044] Advantageously, the crosslinkable composition may be completely free of organic or inorganic powder fillers.
[0045] The term "filler" is used herein to mean one or more individual fillers of reinforcing or non-reinforcing grades for the elastomer in question, homogeneously dispersed in the composition in powder form (as opposed to the nodules of the present invention), and the term "inorganic filler" is used to mean transparent fillers (sometimes called "white fillers"), as opposed to organic fillers such as, for example, carbon black and graphite.
[0046] It should be noted that the composition according to the invention thus contains no carbon black or at most 100 phr (preferably at most 50 phr, or even at most 10 phr, or even at most 5 phr) of carbon black, and that this composition according to the invention may be free of silica, and may optionally contain at most 70 phr of non-reinforcing inorganic fillers, such as, but not limited to, chalk or aluminosilicates such as kaolin.
[0047] According to a first embodiment of the invention, the crosslinking system comprises sulfur and optionally also a peroxide, said at least one elastomer comprising: Functionalized or non-functionalized olefinic rubbers, such as ethylene-α-olefin copolymers, e.g., ethylene-propylene copolymers (EPM) and ethylene-propylene-diene-terpolymers (EPDM); and Functionalized or non-functionalized diene-based rubbers derived at least in part from conjugated diene monomers, such as natural rubber (NR), isoprene homopolymers and copolymers, and butadiene homopolymers and copolymers; A rubber selected from And said thermoplastic polymer phase comprises at least one saturated polymer, preferably chosen from functionalized or non-functionalized, aliphatic or aromatic polyolefins, such as homopolymers or copolymers of ethylene or propylene.
[0048] It should be noted that the sulfur-based crosslinking system contains, in addition to sulfur, all or part of the usual vulcanization accelerators and activators in a known manner.
[0049] Ethylene-α-olefin copolymers for olefinic rubbers may generally include those derived from ethylene and an α-olefin containing from 3 to 20 carbon atoms, preferably from 3 to 12 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 4-methylpentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene. The α-olefins selected from propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene are preferred.
[0050] Copolymers of isoprene and butadiene for diene-based rubbers may include, for example, isoprene-butadiene copolymers (BIR), copolymers of isoprene and / or butadiene with vinyl aromatic comonomers such as styrene (SIR, SBR, SBIR).
[0051] According to one example of this first embodiment of the invention, the at least one elastomer is an EPDM having a mass content of units derived from ethylene of between 15% and 80%, and the thermoplastic polymer phase comprises at least one "aliphatic" polyolefin selected from ethylene homopolymers, propylene homopolymers and polypropylene-ethylene-diene terpolymers having a mass content of units derived from ethylene of between 1% and 15%.
[0052] It should thus be noted that the EPDM that may be used as the elastomer in the composition of the present invention may have a relatively high mass content of units derived from ethylene, between 60% and 80%, or conversely between 15% and 20%. As regards the aliphatic polyolefin forming the thermoplastic phase of the present invention, it may be a "PEDM" that is derived primarily from polypropylene with a mass content of at least 80% (e.g., with 5% to 15% ethylene and 2.5% to 5% diene).
[0053] According to a second embodiment of the invention, the crosslinking system comprises a peroxide and optionally also sulfur, said at least one elastomer is saturated, said phase comprises saturated or unsaturated polymer chains, and preferably said at least one elastomer is a silicone rubber, for example chosen from polydimethylsiloxane (PDMS), and said phase comprises at least one saturated polymer, for example chosen from phenylsilicone or alkylsilicone resins.
[0054] It is noted that the peroxide-based crosslinking system may advantageously include an organic peroxide as the crosslinking agent and a crosslinking coagent including, for example, triallyl cyanurate (TAC) or triallyl isocyanurate (TAIC).
[0055] As silicone rubber any polyorganosiloxane may generally be used, and as saturated polymer any thermoplastic silicone resin, for example of the alkyl (eg methyl) silicone or phenyl silicone type.
[0056] Another subject of the present invention is a crosslinked rubber composition which is the product of thermal crosslinking of a crosslinkable composition as defined above, by chemical reaction with said crosslinking system, said crosslinking being obtainable by setting a temperature between 140 and 220°C, preferably between 150 and 200°C.
[0057] It is noted that the crosslinked composition according to the present invention, like the crosslinkable composition, may have at least one of the above-mentioned morphological characteristics of the particles dispersed in the composition [(a)(i) and / or (a)(ii) and / or (a)(iii)] and / or [(b)(i) and / or (b)(ii)].
[0058] According to another aspect of the present invention, the crosslinked rubber composition comprises: (a) a Shore A hardness, measured according to the ASTM D 2240 standard, of 60 or more, preferably 65 to 70; (b) secant moduli M100, M200, and M300 at 100%, 200%, and 300% strains, measured in uniaxial tension according to the ASTM D 412 standard, greater than 3 MPa, greater than 6 MPa, and greater than 9 MPa, respectively, and preferably greater than 6 MPa, greater than 9 MPa, and greater than 12 MPa, respectively; (c) the modulus ratio M155Hz / M15Hz and the loss tangent tanD at 15Hz, measured at 23°C by frequency sweep on a Metravib® block-type test specimen, according to the ISO 4664 standard, using a Metravib® viscosity analyzer; (i) M155Hz / M15Hz≦1.50; (ii) a dynamic modulus of elasticity at 15 Hz of ≥ 7 MPa; and (iii) tan D ≦ 0.10 at 15 Hz; A coefficient ratio M155Hz / M15Hz and a loss tangent tanD at 15Hz that meets at least one of the conditions (i) and (ii) above; and, (d) 5×10 deformations measured on “mini-diabolos” specimens with a minimum load of 0 N and maximum loads of 250 N, 200 N, 125 N, and 100 N at a frequency of 5 Hz and a temperature of 23° C. using a hydraulic test machine “MTS 831.02 Elastomer Test System” with a maximum capacity of 25 kN, a force cell of 15 kN, and a cylinder with a stroke length of ±60 mm, and controlled by “MTS Flextest 40” software. 6 Over cycle fatigue strength; The composition may have at least one of the characteristics (a), (b), (c), and (d).
[0059] Preferably, these properties (a), (b), (c) and / or (d) are obtained by said first aspect of the invention, i.e. by means of a sulfur-based crosslinking system, said at least one elastomer being an olefinic rubber (e.g. EPM or EPDM) or a diene-based rubber derived from a conjugated diene (e.g. NR), and said thermoplastic phase comprising a saturated polymer (e.g. an aliphatic or aromatic polyolefin, e.g. a homopolymer or copolymer of ethylene or propylene, or polystyrene).
[0060] It should be noted that the hardness and mechanical properties of the crosslinked composition according to the invention are advantageously superior to those of a control composition based on the same raw materials but obtained via the process illustrated in WO2020 / 225498A1 (wherein, accordingly, nodules are added instead of the dispersed filaments or fibrils according to the invention). In particular, the Applicant has confirmed that the crosslinked composition according to the invention has a very significantly increased static modulus compared to that of the control composition obtained according to the examples in WO2020 / 225498A1, and also improved dynamic properties compared to those of said control composition, including a fatigue strength much higher than that of said control composition.
[0061] As indicated above for the crosslinkable compositions, the crosslinked compositions of the present invention may be free of any powder fillers (organic or inorganic).
[0062] According to said second embodiment of the invention, in which said at least one elastomer comprises said silicone rubber, preferably chosen from PDMS, and said thermoplastic phase comprises said at least one saturated polymer, preferably chosen from phenyl or alkyl silicone resins, the crosslinked composition may therefore be completely free of silica.
[0063] Surprisingly, it should be noted that this absence of silica in rubber compositions based on such silicone rubbers (which usually contain silica as a reinforcing filler) means that the high level of reinforcement obtained by the dispersion of phenyl or alkyl silicone resin filaments or fibrils is not reflected in the mechanical nonlinearity observed under dynamic stress, which is favorably reflected in the Payne effect, which is also reduced for this second embodiment compared to a control composition based on the same raw materials (e.g. the same elastomeric matrix and crosslinking system) but filled with carbon black instead of this resin.
[0064] It should also be noted that the mechanical properties described above for the crosslinked compositions of the present invention are not significantly impaired after thermo-oxidative aging (i.e., under hot air) or after aging by exposure to UV radiation.
[0065] The mechanical components with dynamic functions according to the invention are selected from anti-vibration mountings and elastic joints, in particular for automotive or industrial equipment, The member comprises at least one elastic portion made of a crosslinked rubber composition and adapted to be subjected to dynamic stress; And according to the invention, said crosslinked composition is as defined above.
[0066] The sealing element according to the invention is in particular selected from automotive body sealing and architectural sealing profiles, the sealing element includes an elastic portion made of a crosslinked rubber composition; And according to the present invention, said crosslinked rubber composition is as defined above.
[0067] In this case, it should be noted that, for example in gaskets sealing the body of an automobile, it is possible to incorporate in the composition of the invention up to 100 phr of carbon black and 10 to 60 phr of inorganic fillers other than silica (for example chalk or aluminosilicates such as kaolin) in combination with metal oxides (for example calcium oxide).
[0068] The process for preparing the crosslinkable composition according to the invention defined above comprises the steps of: a) in an internal mixer, for example of the tangential or intermeshing type (i.e. with interlocking rotors) or in a screw extruder, for example of a twin screw type, a0) introduction of said at least one elastomer, and then introduction of said other ingredients except for said crosslinking system; a1) thermomechanical processing, including melt kneading the reaction mixture excluding the crosslinking system, to produce a precursor mixture of the crosslinkable composition; a2) heating the reaction mixture to a maximum temperature Ta of the reaction mixture, the maximum temperature Ta being higher than the melting point Tf or softening point Tr of at least one of the thermoplastic polymer phases, preferably with a difference Ta-Tf or difference Ta-Tr of 1-100°C; a3) stabilizing the heating for a holding time of at least 10 seconds, preferably between 20 seconds and 5 minutes; a4) extracting the precursor mixture from the internal mixer or screw extruder; Next, b) The mechanical working of the precursor mixture in an external roller mixer or in a conical twin-screw device for producing the crosslinkable rubber composition with the addition of the crosslinking system containing sulfur and / or peroxide, wherein the temperature Tb of the precursor mixture is temporarily higher than the crystallization temperature Tc when the thermoplastic polymer phase is partially crystalline, and temporarily higher than the glass transition temperature Tg when the thermoplastic polymer phase is amorphous, in such a manner; comprises.
[0069] Preferably, step b) is started at the maximum initial temperature Tb0 of the precursor mixture, and Tb0 > Tc or Tb0 > Tg when the thermoplastic phase is partially crystalline or amorphous, respectively.
[0070] More preferably, step b) is started while the thermoplastic phase softens and is in a molten state, for example, in the precursor mixture, and involves the temperature Tb dropping to Tb < Tc or Tb < Tg.
[0071] Even more preferably, the extraction of the precursor mixture from the closed kneader or screw extruder and the start of the mechanical working in step b) (after the transfer of the precursor mixture into the external roller mixer or conical twin-screw device) are separated by a time interval Δt, and step b) follows step a4) in such a manner that a temperature difference ΔT = Tt - Tb0 between the dropping temperature Tt (e.g., "sharp dropping") of the precursor mixture at the end of step a4) and the initial temperature Tb0 at the start of step b) is brought about such that ΔT / Tt < 30%, and preferably ΔT / Tt < 20%.
[0072] Advantageously, Δt < 10 minutes, and for example Δt < 2 minutes, such that ΔT / Tt < 10%, and for example ΔT / Tt < 1%.
[0073] It should be noted that in this manner, by being subjected to generally continuous shear from step a1) to the end of step b), the precursor mixture is essentially cooled by the mechanical processing of step b) at the end of step a4).
[0074] Regarding step a2) of the process of the invention, the difference Ta-Tf or Ta-Tr, as the case may be, is advantageously between 5 and 100°C, preferably between 10 and 70°C.
[0075] It should be noted that the value chosen for Ta will therefore depend on the values of Tf or Tr characterizing the thermoplastic polymer phase used; if the thermoplastic polymer phase is based on an aliphatic polyolefin such as a propylene homopolymer or copolymer, Ta may for example be between 160 and 220°C, preferably between 170 and 200°C, whereas if this thermoplastic phase is an alkyl or phenyl silicone resin, Ta may for example be between 70 and 150°C, preferably between 80 and 120°C.
[0076] Advantageously, the heating of step a2) is In the internal mixer, For example, the rotor blade speed in an internal mixer is between 10 and 200 rpm, preferably between 50 and 120 rpm, and the mixer is operated for at least 80 seconds. -1 , preferably at least 150 seconds -1 shear rate of the reaction mixture in the internal mixer; and / or A jacket in the internal mixer for receiving a heat transfer fluid; and / or Use of internal mixer filling levels of more than 100%; or an extruder-mounted heating element within said screw extruder; This can be implemented using
[0077] Such shear rates (e.g., 100 to 300 s -1It should be noted that the tangential (eg Banbury type) or intermeshing (Haake type) internal mixers can be used.
[0078] It should also be noted that a speed of 200 rpm is particularly suitable for a Haake kneader, while a speed of about 100 rpm is more suitable for a Shaw 3.6L kneader.
[0079] With regard to the mechanical processing step b) according to the invention, it should be noted that it may also be carried out other than in an external roller mixer or a conical twin screw apparatus, provided that the precursor mixture resulting from step a4) is immediately cooled solely by the mechanical processing of step b) and passes from a molten, softened or at least non-crystalline initial state to a crystalline state (in the case of a partially crystalline thermoplastic phase) or from a softened or at least non-glassy initial state to a glassy state (in the case of an amorphous thermoplastic phase) by being subjected to a generally continuous shear between step a4) and the end of step b).
[0080] BRIEF DESCRIPTION OF THE DRAWINGS Other characteristics, advantages and details of the invention will become apparent on reading the following description of some embodiments of the invention, given by way of non-limiting illustration in relation to the attached drawings, in which:
[0081] (Figure 1)
[0021] FIG. 1 is a relative enthalpy-temperature graph showing the thermal behavior of "PPH3060" polypropylene forming the thermoplastic polymer phase in crosslinkable composition I according to the invention and in control crosslinkable composition C3.
[0082] (Figure 2) [Figure 2] is an infrared camera image of the precursor mixture of the crosslinkable composition I according to the invention at the outlet of the internal mixer used in step a).
[0083] (Figure 3) [Figure 3] is an infrared camera image of the crosslinkable composition I according to the invention at the outlet of the external mixer used in step b).
[0084] [Figure 4] [Figure 4] is a graph showing the evolution of the temperature of each precursor mixture of the crosslinkable composition I and the crosslinkable composition C3 as a function of time during the mechanical processing step b), these temperatures being measured from an initial moment t0 = 0 min 0 s, which corresponds to the initial temperature Tb0 of each precursor mixture at the start of step b).
[0085] [Figure 5] [Figure 5] is a first image showing the three-dimensional morphological characteristics (axis in nm) of the dispersion in the form of polypropylene nodules forming the thermoplastic polymer phase of the control crosslinked composition C3, obtained by segmentation via FIB-SEM Focused Ion Beam (FIB) Scanning Electron Microscopy (SEM) technique.
[0086] [Figure 6] [Figure 6] is a second image showing the two-dimensional morphological features (in nm) of the dispersion in the form of polypropylene nodules in the control crosslinked composition C3, obtained by segmentation via the same FIB-SEM technique.
[0087] [Figure 7] [Figure 7] is a first image showing the three-dimensional morphological characteristics (in nm) of a dispersion in the form of polypropylene filaments or fibrils forming the thermoplastic phase of crosslinked composition I according to the invention, obtained by segmentation via the same FIB-SEM technique as in Figure 5.
[0088] [Figure 8] [Figure 8] is a second image showing the two-dimensional morphological features (in nm) of a dispersion in the form of polypropylene filaments or fibrils in crosslinked composition I according to the present invention, obtained by segmentation via the same FIB-SEM technique as in Figure 6.
[0089] [Figure 9] [Figure 9] shows the volume distribution of the equivalent diameter of the filaments or fibrils of the crosslinked composition I according to the invention and the equivalent diameter of the nodules of the control crosslinked composition C3 after analysis by FIB-SEM, the equivalent diameters being weighted by their volume fraction in the total amount of dispersed polypropylene.
[0090] (Figure 10) [Figure 10] is a diagram showing the numerical distribution of aspect ratios of filaments or fibrils of crosslinked composition I according to the present invention and the numerical distribution of aspect ratios of nodules of control crosslinked composition C3 after analysis by FIB-SEM.
[0091] (Figure 11) [Figure 11] shows the correlation between the aspect ratio of particles (i.e., filaments or fibrils for I and nodules for C3) and their equivalent diameters measured for crosslinked composition I of the present invention and for the control crosslinked composition C3 after analysis by FIB-SEM.
[0092] (Figure 12) [Figure 12] is a graph comparing the stress-strain characteristic curves of the crosslinked composition I according to the invention and of the control crosslinked compositions C1, C2, and C3.
[0093] (Figure 13) [Figure 13] is a graph of the fatigue strength versus the applied force, which compares the curves of the number of cycles without fracture as a function of the magnitude of the applied force for the crosslinked composition I according to the invention and the control crosslinked composition C2.
[0094] [Example of the present invention] In the examples shown below, Control crosslinkable compositions C1, C2, and C3 based on the same natural rubber (NR), where C1 is unreinforced, C2 is reinforced only with carbon black, and C3 is reinforced only with polypropylene (hereinafter abbreviated as PP) nodules; a crosslinkable composition I according to the invention based on the same natural rubber and the same other raw materials as composition C3, but reinforced with the same PP nanofilaments or nanofibrils instead of said nodules and obtained through a mixing process different from that used for composition C3, as explained below; was prepared.
[0095] Table 1 details the formulations, in phr (parts by weight per 100 parts of NR elastomer), of the masterbatches (consisting of the precursor mixture obtained by the thermomechanical processing step a) and before the mechanical processing step b) and the addition of the crosslinking system) and of the crosslinkable compositions C1 to C3 and I derived from these masterbatches.
[0096] [Table 1]
[0097] As shown in FIG. 1, the enthalpy diagram of the PP “PPH3060” used in compositions C3 and I for producing particles dispersed in a NR matrix shows, on the one hand, a melting point Tf of the PP (upper endothermic transition peak) of about 165° C., and, on the other hand, a crystallization temperature Tc of the PP (lower exothermic transition peak) of 100-110° C.
[0098] As used herein, the thermal behavior of a thermoplastic polymer phase, for example of "PPH3060" (density of 0.905, measured according to the ISO 1183 standard), including the measured temperatures Tf, Tr, Tc, and Tg, is measured by differential scanning calorimetry ("DSC" according to the ISO 11357 standard), as described below: Programming: double sweep from -80°C to 250°C at 20°C / min under 50mL / min N2 with 5 min isotherm at each steady stage; Repeatability: 2 tests / specimen; Equipment: DSC with heat flow DSC1 "Mettler-Toledo"; Calibration: Mettler-Toledo specific procedure with standards: N-octane / indium / zinc; was obtained.
[0099] The above-mentioned crosslinkable compositions C1 to C3 and I are Step a) A 3160 cm 2 centrifuge with interlocking rotors using a packing factor of 1.00 for composition C2 and 1.10 for compositions C3 and I. 3 Thermomechanical processing in a "Shaw" internal mixer; Step b) mechanical processing on a "Comerio" open roll mixer (commonly known as the "acceleration step"); The mixture was prepared by carrying out the following procedure.
[0100] More precisely, the following successive steps were carried out to prepare each of compositions C1-C2, C3 and I, as detailed in the three processes detailed below:
[0101] <Preparation of each of the two polypropylene-free compositions C1 to C2> Filling of internal mixers; t=0 minutes; Material:NR; Speed: 50 rpm; T 調節 =80℃.
[0102] plasticization; t 合計 =1 minute; material:-; Speed: 50 rpm; T 調節 =80℃.
[0103] filling; t 合計 =1 minute; Materials: (for composition C2) filler + (for compositions C1-C2) additive; Speed: 50 rpm; T 調節 =80℃.
[0104] Kneading; t+1 min; material:-; Speed: 50 rpm.
[0105] Kneading with self-heating; t 合計 =[3 minutes; 3 minutes 30 seconds]; material:-; Speed: 96 rpm; T 自己加熱 =150℃.
[0106] Dropping the mixture.
[0107] Cooling in an open roll mixer; t=0; time=1min; T 調節 =20°C.
[0108] Acceleration on open mixer rolls; The cross-linking system was added after t = 3 min.
[0109] <Preparation of composition C3 containing polypropylene nodules> Filling of internal mixers; t=0 minutes; Material:NR; Rotation speed: 50 rpm; and T 調節 =80℃.
[0110] plasticization; t 合計 =1 minute; material:-; Speed: 50 rpm; and T 調節 =80℃.
[0111] filling; t 合計 =1 minute; Material: PP+additives; Speed: 50 rpm; and T 調節 =80℃.
[0112] Kneading with self-heating; t 合計 =[3 minutes; 3 minutes 30 seconds]; material:-; Speed: 96 rpm; and T 自己加熱 =140°C.
[0113] Maintaining self-heating; Hold temperature for 30 seconds; Speed: 96 rpm.
[0114] Dropping the mixture.
[0115] cooling; Approximately 24 hours; and T 調節 =20℃.
[0116] Transfer of the cooled mixture to an open mixer and acceleration; Addition of crosslinking system after t=3 min on roll.
[0117] <Preparation of composition I containing polypropylene filaments or fibrils> Filling of internal mixers; t=0 minutes; Material:NR; Speed: 50 rpm; and T 調節 =80℃.
[0118] plasticization; t 合計 =1 minute; material:-; Speed: 50 rpm; and T 調節 =80℃.
[0119] filling; t 合計 =1 minute; Material: PP+additives; Speed: 50 rpm; and T 調節 =80℃.
[0120] Kneading with self-heating; t 合計 =[3 minutes; 3 minutes 30 seconds]; material:-; Speed: 96 rpm; and T 自己加熱 =140°C.
[0121] Maintaining self-heating; Hold temperature for 30 seconds; Speed: 96 rpm.
[0122] Dropping the mixture.
[0123] Instant cooling in an open roll mixer; t = 0: mixture extracted from the internal mixer; Introduction on roll: T 調節 = 20°C, 1 min after extraction.
[0124] Acceleration on the rolls of an open mixer; The cross-linking system was added after t = 3 min.
[0125] Steps a) and b) carried out on crosslinkable compositions C3 and I Table 2 below compares the performance of the thermomechanical kneading step a) and the mechanical processing step b) for crosslinkable compositions C3 and I as a function of the control temperature used and of the temperature measured precisely at the core of the precursor mixture.
[0126] [Table 2]
[0127] More specifically, it should be noted that all temperatures measured between steps a) and b) (i.e., indicated with "Measured" in column 2 for compositions C3 and I) were precisely measured in each precursor mixture of compositions C3 and I.
[0128] The image in FIG. 2 shows the appearance of the precursor mixture of crosslinkable composition I according to the invention at the outlet of the internal mixer, and the image in FIG. 3 shows the appearance of this composition I after acceleration on the rolls of the open mixer (i.e. at the end of the mechanical processing), these images being obtained by a "FLIR SC660" high-resolution infrared camera.
[0129] Thus, composition I according to the invention was extracted from the internal mixer at a temperature of 171° C., which was the “fast dropping” temperature taken at the core of the precursor mixture using a “Testo 925” pyrometer. The precursor mixture of composition I was then immediately deposited on an open roll mixer.
[0130] As shown in the graph in Figure 4, the initial temperature Tb0 of 170°C at the core of the precursor mixture at t0=0 (initial moment of mechanical processing) decreased during about the first 3 minutes of kneading until it stabilized at about 70°C (see the almost linear decrease in the temperature Tb of the precursor mixture of composition I in this example, and then the obvious slowdown of this decrease just before the 3 minutes of processing). The crosslinking system was added about 3 minutes after t0.
[0131] Thus, the PP contained in the precursor mixture of composition I was processed first in the liquid state and then during its crystallization carried out under shear (at about 100-110° C.), i.e. according to the invention as generally defined herein, resulting in the above-mentioned nanofilaments or nanofibrils homogeneously dispersed in the crosslinkable composition I, as shown in Figures 7 and 8.
[0132] It should be noted that the kinetics of cooling through the process of the present invention, which in the example shown in FIG. 4 for composition I is defined by a continuously decreasing and then substantially constant temperature over time, reflected by a generally convex (i.e., having an upward concavity) curve, nevertheless depends on the amount of precursor mixture and the equipment used for mechanical processing (roll dimensions, temperature regulator power, etc.).
[0133] In contrast to this process, after step a) of the thermomechanical processing in the internal kneader, the precursor mixture of the crosslinkable composition C3 was left to cool for 20 hours without any shear (i.e. cooled statically in ambient air for approximately one day), during which the temperature of the precursor mixture of the composition C3 dropped from 168.9°C (the "fast dropping" temperature, i.e. the temperature of the extraction of the precursor mixture from the internal kneader) to 23°C (the temperature Tb0 of the start of the mechanical processing at t0=0) and the PP crystallized at about 100-110°C in static conditions (i.e. without any shear), contrary to the general principle of the invention defined above.
[0134] Thus, mechanical processing was started on an open roll mixer at room temperature (Tb0=23° C.), then the addition of the crosslinking system about 3 min after t0 caused self-heating of the C3 precursor mixture up to about 70° C., but without a transition above the PP melting point (Tf of 165° C.). Thus, the morphological characteristics of the roughly spherical or ellipsoidal nodules of composition C3 obtained during the thermomechanical processing in step a) were preserved, as shown in FIGS. 5-6.
[0135] It can be seen in FIG. 4 that the kinetics of cooling via the non-inventive process used for control composition C3, which is defined over time by a continuously increasing and then substantially constant temperature, is very different from the kinetics characterizing composition I of the invention, and is even reflected by a substantially opposite (on either side of the horizontal line defined by the final temperature of 70° C.) generally concave curve (i.e., having a downward-pointing concavity).
[0136] <Vulcanization of Control Compositions C1 to C3 and Composition I of the Present Invention> Table 3 below details the vulcanization conditions followed for compositions C1 to C3 and I (temperature of 155° C. for 20 minutes).
[0137] [Table 3]
[0138] <Morphological Characterization of Crosslinked Compositions C3 and I> As described below, the morphological features of Compositions C3 and I were analyzed by segmentation via the Focused Ion Beam (FIB) - Scanning Electron Microscope (SEM) FIB-SEM technique.
[0139] <Specimen Preparation> Each specimen was first surface-treated by cryo-ultramicrotomy to obtain a flat surface. The resulting surface was brought into contact with a 4% osmium tetroxide solution in water for 3 days. After rinsing, a second surface treatment of the cryo-ultramicrotomy-treated area was performed to remove the surface layer damaged by direct contact with osmium.
[0140] <Implementation of FIB-SEM Technique> FIB-SEM ACQUISITION (XB540 Zeiss, "Atlas V software"); SEM: 1.5 kV, 149 pA, exposure time per voxel: 0.3 microseconds; Average per line: 18; Voxel size: 10 nm; Detector: EsB; FIB: 30 kV, 300 pA, polishing rate: 6.6 nm per minute; 3D Tracking: exposure time per voxel: 0.6 microseconds; Average per line: 20; Volume: 20 x 5 x 4 μm; - Pretreatment: Average non-local noise removal - patch7, search21, similarity 0.5; Normalization, C and B correction; Z resampling to 10 nm (cube); Equalization, median filter; - Segmentation: Machine learning ("Ilastik"); Resample to 20nm; PP phase of aperture 1; Global and individual analysis using "AVIZO".
[0141] The images in Figures 5-6, in conjunction with the diagrams in Figures 9-11, show the morphological characteristics of the generally spherical or ellipsoidal nodules dispersed in the crosslinked composition C3 (morphological characteristics that also characterize the composition C3 in the crosslinkable state obtained following the mechanical processing step b) prior to crosslinking). As explained above, Each measured equivalent diameter refers to the diameter of a hypothetical spherical particle with the same volume as the observed particle (the "mean equivalent diameter" refers to the arithmetic number mean of the equivalent diameters of the particles for a sample divided into classes, and the "median equivalent diameter" refers to the median of the volume distribution d 50 (showing); The aspect ratio represents the ratio of the maximum length to the minimum width of each particle observed, the width being assimilated to the minimum diameter in the case of ellipsoidal nodules or generally cylindrical filaments (the term "average aspect ratio" refers to the arithmetic number-average aspect ratio of the particles); and The term "volume fraction of total PP" (y-axis in Figure 9) means the ratio of the total volume of class X particles to the total volume of PP (multiplying the ratio by 100 gives this fraction in %).
[0142] Table 4 below details the individual analyses carried out to quantify the morphological characteristic parameters of the PP nodules in crosslinked composition C3 and the morphological characteristic parameters of the dispersed filaments or fibrils in crosslinked composition I.
[0143] [Table 4]
[0144] These parameters demonstrate a significant difference between the nanofilaments or fibrils of reduced equivalent diameter that characterize the dispersion of PP in composition I of the invention and the spherical or ellipsoidal nodules that characterize the dispersion of PP in control composition C3.
[0145] <Standards and procedures followed for testing of compositions C1-C3 and I> (Standardized measurements) Moving Die Rheometer (MDR): according to ISO6502:2016 standard; Shore A hardness: according to ASTM D 2240; Tensile test: according to ASTM D 412; (Dynamic Mechanical Analysis (DMA) Test) For these "DMA tests" Metravib® viscosity analysis was used and the ISO 4664 standard was followed: Conditions: -10% ±0.1% at 155Hz and -10% ±2% at 15Hz; Test specimen: Metravib (registered trademark) block type; Number of specimens: 3 per condition; Measurement temperature: 23℃; Lubricant: silicone oil spray; (Fatigue strength) The elastomer test system used was an MTS 831.02 hydraulic endurance machine with a maximum capacity of 25 kN, a 15 kN force cell and a cylinder with a stroke length of ±60 mm. Tests were run with MTS Flextest 40 software. The following were used: "mini-diabolos" specimens, 2-3 per condition; A minimum load of 0N, a maximum load defined by four conditions: 250N, 200N, 125N, or 100N; and A frequency of 5Hz, and a temperature of 23°C.
[0146] Testing of control compositions C1-C3 and crosslinked composition I of the invention The above-mentioned morphological characteristics of the thermoplastic phase dispersed in the crosslinked composition I according to the present invention (as shown in Figures 7-8 and 9-11) make it possible, via the above-mentioned mixing process, to impart an overall improved reinforcement to the composition I compared to the three control compositions C1-C3, as shown by the mechanical properties of the composition I relative to the three control compositions C1-C3.
[0147] In particular, the hardness and tensile tests (stress-strain curves of compositions C1-C3 and I are collated in FIG. 12 and the results are detailed in Table 5 below) confirm this improved reinforcement of composition I, especially compared to composition C3, characterized by the same mass (and volume) fraction of PP.
[0148] The tensile curves in FIG. 12 show the reinforcement obtained for composition I, which is clearly superior to that of the unreinforced composition C1 and to that of the composition C3 reinforced with PP nodules, and which is also comparable to that of the composition C2 reinforced only with carbon black.
[0149] [Table 5]
[0150] In particular, this Table 5 shows: The Shore A hardness of the composition I of the invention was 37% higher than that of the composition C3 reinforced with PP nodules, as well as 8% higher than that of the composition C2 reinforced with carbon black; The coefficients M100, M200 and M300 of the composition I of the invention are much higher than those of the composition C3 (by 300%, 197% and 123%, respectively) and higher than those of the composition C2 (see M100 and M200) or comparable to those of the composition C2 (see M300); and The rupture properties of composition I according to the invention were satisfactory and generally comparable to those of compositions C2 and C3.
[0151] Table 6 below details the dynamic properties obtained for compositions C1-C3 and I by the "DMA" dynamic mechanical analysis described above.
[0152] [Table 6]
[0153] These dynamic properties show a significant increase in the dynamic modulus at 15 Hz, the dynamic modulus at 155 Hz and the M155 / M15Hz ratio of composition I according to the present invention compared to composition C3 reinforced with PP nodules (77% increase for M15Hz and 99% increase for M155Hz), which is favorably reflected in the reduced mechanical nonlinearity in the frequency sweep of composition I according to the present invention compared to composition C3.
[0154] Fatigue strength tests carried out as explained above, the results of which are shown in FIG. 13 (with the number of cycles without break on the x-axis and the force in N on the y-axis) for crosslinked compositions C2 and I, show superior fatigue strength of the specimens made of composition I of the invention compared to the specimens made of composition C2 reinforced with carbon black. In particular, composition I showed a fatigue strength increased by about 2.5 times with respect to composition C2 for high stresses (see, for example, forces of 250 N or 200 N). For lower forces, composition I of the invention had a fatigue strength of more than 5 million cycles without break (the test was stopped at 5 million cycles), while composition C2 broke after only about 500,000 cycles. [Brief description of the drawings]
[0155] [Figure 1] 1 is a relative enthalpy-temperature graph showing the thermal behavior of "PPH3060" polypropylene forming the thermoplastic polymer phase in crosslinkable composition I according to the invention and in control crosslinkable composition C3. [Diagram 2] FIG. 2 is an infrared camera image of the precursor mixture of the crosslinkable composition I according to the invention at the outlet of the internal kneader used in step a). [Diagram 3] 3 is an infrared camera image of the crosslinkable composition I according to the invention at the outlet of the external mixer used in step b). [Figure 4] Graph showing the evolution of the temperature of the precursor mixtures of the crosslinkable composition I and of the crosslinkable composition C3, respectively, as a function of time during the mechanical working step b). [Diagram 5] FIB-SEM: First image showing the three-dimensional morphological features (axis in nm) of the dispersion in the form of polypropylene nodules forming the thermoplastic polymer phase of the control crosslinked composition C3, obtained by segmentation via focused ion beam (FIB) scanning electron microscopy (SEM) technique. [Figure 6] FIG. 2 is a second image showing the two-dimensional morphological features (in nm) of the dispersion in the form of nodules of polypropylene in the control crosslinked composition C3, obtained by segmentation via the same FIB-SEM technique. [Figure 7] FIG. 6 is a first image showing the three-dimensional morphological features (in nm) of a dispersion in the form of polypropylene filaments or fibrils forming the thermoplastic phase of crosslinked composition I according to the invention, obtained by segmentation via the same FIB-SEM technique as in FIG. 5 . [Figure 8] FIG. 7 is a second image showing the two-dimensional morphological characteristics (in nm) of a dispersion in the form of polypropylene filaments or fibrils in a crosslinked composition I according to the present invention, obtained by segmentation via the same FIB-SEM technique as in FIG. 6 . [Figure 9] FIG. 2 shows the volume distribution of the equivalent diameter of the filaments or fibrils of the crosslinked composition I according to the invention and of the equivalent diameter of the nodules of the control crosslinked composition C3 after analysis by FIB-SEM. [Figure 10] FIG. 2 shows the numerical distribution of aspect ratios of filaments or fibrils of crosslinked composition I according to the invention and of nodules of control crosslinked composition C3 after analysis by FIB-SEM. [Figure 11]FIG. 1 shows the correlation between the aspect ratio of particles (i.e., filaments or fibrils for I and nodules for C3) and their equivalent diameters measured for crosslinked composition I of the present invention and for the control crosslinked composition C3 after analysis by FIB-SEM. [Figure 12] 1 is a graph comparing the stress-strain characteristic curves of a crosslinked composition I according to the invention and of control crosslinked compositions C1, C2, and C3. [Figure 13] 1 is a graph of the fatigue strength versus the applied force, which plots the curves of the number of cycles without break as a function of the magnitude of the applied force for a crosslinked composition I according to the invention and for a control crosslinked composition C2.
Claims
1. A crosslinkable rubber composition (I) based on at least one elastomer, said composition (I) comprises other ingredients including a crosslinked system and a thermoplastic polymer phase having at least one melting point Tf or softening point Tr, a glass transition temperature Tg and, if said phase is partially crystalline, a crystallization temperature Tc; said phase being dispersed in said at least one elastomer in the form of particles; said crosslinking system comprises sulfur if said at least one elastomer is unsaturated and said phase comprises saturated polymer chains, and comprises a peroxide if said at least one elastomer is saturated; The crosslinkable rubber composition (I) is a) a melt reaction to obtain a precursor mixture of said crosslinkable composition (I) by thermomechanical processing of a reaction mixture comprising said at least one elastomer and said other ingredients, except for said crosslinking system, said melt reaction comprising heating said reaction mixture to a maximum temperature Ta of said reaction mixture higher than said at least one melting point Tf or softening point Tr; then b) mechanical processing of the precursor mixture with the addition of the crosslinking system to produce the crosslinkable composition (I); including the product of the particles include filaments or fibrils; The temperature Tb of the precursor mixture during the mechanical processing in step b) is temporarily greater than the crystallization temperature Tc if the phase is partially crystalline or the glass transition temperature Tg if the phase is amorphous.
2. The mechanical processing of step b) is started at an initial temperature Tb0 of the precursor mixture, When the phase is partially crystalline or amorphous, Tb0>Tc or Tb0>Tg, respectively; 2. The crosslinkable rubber composition (I) according to claim 1, wherein the mechanical processing of step b) is preferably initiated while the thermoplastic polymer phase is in a molten or softened state in the precursor mixture.
3. 3. The crosslinkable rubber composition (I) according to claim 2, wherein the temperature Tb of the precursor mixture during step b) is highest when mechanical processing begins, where Tb=Tb0, and then drops to Tb<Tc, or Tb<Tg, when the phase is partially crystalline, or amorphous, respectively.
4. step b) follows step a) in such a way that the extraction of said precursor mixture at the end of step a) and the start of the mechanical processing in step b) after the transfer of said precursor mixture are separated by a time interval Δt, The crosslinkable rubber composition (I) according to claim 2 or 3, which provides a temperature difference ΔT=Tt-Tb0 between the dropping temperature Tt of the precursor mixture at the end of step a) and the initial temperature Tb0 at the beginning of step b), such that ΔT / Tt<30%, and preferably ΔT / Tt<20%.
5. Δt<10 minutes, and preferably Δt<2 minutes, so that ΔT / Tt is less than 10%, and for example ΔT / Tt<1%, 5. The crosslinkable rubber composition (I) according to claim 4, in such a way that the precursor mixture is subjected to a generally continuous shear from the beginning of step a) to the end of step b), and then, at the end of step a), is cooled essentially by the mechanical processing in step b).
6. The mechanical processing is started at the initial temperature Tb, the initial temperature Tb is between Tc or Tg, depending on whether the phase is partially crystalline or amorphous, respectively, and the maximum temperature Ta of the reaction mixture, which corresponds to the dropping temperature Tt of the precursor mixture; Preferably, Tb0 is 110 to 220°C. The crosslinkable rubber composition (I) according to any one of claims 2 to 5.
7. Tb0 is 150 to 190° C., The phase may be partially crystalline, e.g., comprising a propylene homopolymer or copolymer, or may be amorphous, e.g., comprising a polystyrene; The temperature Tb of the precursor mixture is highest at the start of mechanical processing, where Tb=Tb0, and then decreases until Tb is between 10 and 90° C. Preferably, said crosslinking system is added to said precursor mixture after a homogenization time of said precursor mixture, counted from the start of mechanical processing, The crosslinkable rubber composition (I) according to claim 6, wherein the homogenization time is, for example, 1 minute to 5 minutes.
8. The particles are (a) their equivalent diameter, defined as the diameter of a hypothetical spherical particle of the same volume; (i) for all said particles, an equivalent diameter ranging from 5 nm to 1000 nm, and preferably from 10 nm to 330 nm; (ii) a median equivalent diameter of 20 nm to 200 nm, preferably 30 nm to 60 nm; and (iii) an average equivalent diameter of 30 nm to 300 nm, and preferably 40 nm to 70 nm; and / or (b) their aspect ratio, defined as the ratio of the longest length to the shortest width of each of said particles; (i) an average aspect ratio of 2 or greater, and preferably from 2.0 to 2.5; and (ii) a maximum aspect ratio for all said particles greater than 5, and preferably between 10 and 15; and having at least one morphological characteristic of Also preferably, the particles comprise filaments or fibrils with a volume fraction of more than 70%, such as more than 80%.
9. A crosslinked rubber composition comprising: The crosslinked rubber composition is the product of thermal crosslinking of the crosslinkable rubber composition (I) according to any one of claims 1 to 8 by chemical reaction with the crosslinking system, The crosslinked rubber composition comprises (a) a Shore A hardness, measured according to the ASTM D 2240 standard, of 60 or more, preferably 65 to 70; (b) secant moduli M100, M200, and M300 at 100%, 200%, and 300% strain, measured in uniaxial tension according to ASTM D 412 standard, greater than 3 MPa, greater than 6 MPa, and greater than 9 MPa, respectively, and preferably greater than 6 MPa, greater than 9 MPa, and greater than 12 MPa, respectively; (c) the modulus ratio M155Hz / M15Hz and the loss tangent tanD at 15Hz measured at 23°C by frequency sweep on a Metravib® block-type test specimen using a Metravib® viscosity analyzer according to the ISO 4664 standard; (i) M155Hz / M15Hz≦1.50, (ii) a dynamic modulus at 15 Hz of ≥ 7 MPa; and (iii) tan D≦0.10 at 15 Hz; a coefficient ratio M155Hz / M15Hz and a loss tangent tanD at 15Hz that satisfies at least one of the above conditions (i) and (ii); and, (d) 5×10 measured on “mini-diabolos” specimens with a minimum load of 0 N and maximum loads of 250 N, 200 N, 125 N, and 100 N, at a frequency of 5 Hz and a temperature of 23° C. using a hydraulic endurance machine “MTS 831.02 Elastomer Test System” with a maximum capacity of 25 kN, a force cell of 15 kN and a cylinder with a stroke length of ±60 mm, and operated with “MTS Flextest 40” software. 6 Fatigue strength over cycles; The crosslinked rubber composition has at least one of the following characteristics:
10. Mechanical parts with dynamic functions, selected from anti-vibration supports and elastic joints, in particular for automotive or industrial equipment, The member comprises at least one elastic portion made of a crosslinked rubber composition suitable for being subjected to dynamic stress; The crosslinked rubber composition according to claim 9 , which is a mechanical member.
11. A sealing element, in particular chosen from automotive body sealing and architectural sealing profiles, the sealing element includes an elastic portion made of a crosslinked rubber composition; The sealing element, wherein the crosslinked rubber composition is the crosslinked rubber composition of claim 9.
12. A process for preparing the crosslinkable rubber composition (I) according to any one of claims 1 to 8, comprising the steps of: The process comprises: a) in an internal mixer, for example of the tangential or intermeshing type, or in a screw extruder, for example of the twin screw type, a0) introduction of said at least one elastomer, and then introduction of said other ingredients except said crosslinking system; a1) thermomechanical processing in the internal mixer or in the screw extruder, including melt mixing of the reaction mixture excluding the crosslinking system, to produce a precursor mixture of the crosslinkable rubber composition (I); a2) heating the reaction mixture to a maximum temperature Ta of the reaction mixture, said maximum temperature Ta being higher than said at least one melting point Tf or softening point Tr of said thermoplastic polymer phase, preferably with a difference Ta-Tf or difference Ta-Tr of 1 to 100°C; a3) stabilizing the heating for a holding time of at least 10 seconds, preferably between 20 seconds and 5 minutes; a4) extracting the precursor mixture from the internal mixer or screw extruder; Next, b) mechanical processing of the precursor mixture in an external roller mixer or in a conical twin screw apparatus to produce the crosslinkable rubber composition (I) with the addition of the crosslinking system comprising sulfur and / or peroxide, in such a way that the temperature Tb of the precursor mixture is temporarily greater than the crystallization temperature Tc if the thermoplastic polymer phase is partially crystalline and temporarily greater than the glass transition temperature Tg if the thermoplastic polymer phase is amorphous; The process includes:
13. Step b) is initiated at a maximum initial temperature Tb0 of the precursor mixture, Tb0>Tc, or Tb0>Tg, when the thermoplastic polymer phase is partially crystalline or amorphous, respectively; 13. The process for preparing a crosslinkable rubber composition (I) according to claim 12, wherein step b) is preferably initiated while the thermoplastic polymer phase is in a softened and, for example, molten state in the precursor mixture, and the temperature Tb is lowered until Tb<Tc, or Tb<Tg.
14. Step b) follows step a4) in such a way that the extraction of the precursor mixture from the internal mixer or screw extruder and the start of the mechanical processing in step b) after the transfer of the precursor mixture into the external roller mixer or conical twin screw device are separated by a time interval Δt, 14. Process for preparing a crosslinkable rubber composition (I) according to claim 13, resulting in a temperature difference ΔT=Tt-Tb0 between the dropping temperature Tt of the precursor mixture at the end of step a4) and the initial temperature Tb0 at the beginning of step b), such that ΔT / Tt<30%, and preferably ΔT / Tt<20%.
15. For ΔT / Tt less than 10%, e.g., for ΔT / Tt<1%, Δt<10 minutes, and for example, Δt<2 minutes; 15. The process for preparing a crosslinkable rubber composition (I) according to claim 14, wherein the precursor mixture is cooled at the end of step a4) essentially by the mechanical processing in step b) by being subjected to a generally continuous shear from step a1) to the end of step b).